Changes in Land Cover Analysis in The Gulf Coast Kendari Using High Resolution Satellite Image (Period: 2003-2009) - Jaya, Laode Muh. Golok (Universitas Muhammadiyah Surakarta, 2013)
This research was aimed to indentify land cover change in coastal area of Kendari Bay in period 2003 to 2009. The satellite imagery data (Ikonos and Quick Bird) collected in 2003 and 2009 were used in this research to obtain the land cover change. The method used in this research was comparing the classification of satellite imagery. Field survey was conducted using handheld GPS for ground truth.Â The result of this research showed us the land use change in period 2003-2009. Mangrove vegetation decreased 56.57 Ha and the fishpond also decreased 205.5 Ha. The primary forest decreased into 3.28 Ha in year 2009. The secondary forest also decreases 124.84 Ha. In the same time the urban area increased from 382.37 Ha in year 2003 to 674.37 Ha in 2009. The land use change also occured for the public space which increased from 6.49 Ha in 2003 to 18.46 Ha in 2009 or increased 11,97 Ha.